The perception of discomfort before and after cold water immersion among school children - Laakso, B.; Hagerup, A. J. T.; Horneman, E. L.; Nysted, H. P. L.; Stallman, R. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION Norway is subjected to harsh winters. Drowning after falling through the ice is an ever present risk. Water safety therefore, must include safety on the ice, exposure to cold water and how to exit the water under such circumstances. Activity on the ice of the lake and cold water exposure has been incorporated into the curriculum of Vingrom Elementary School. The school itself is located just 800 meters from the lake, increasing the exposure of pupils, necessitating the inclusion of knowledge of cold water exposure in their curriculum.